Postnasal Drip and Nasal Endoscopy: Localization and Association With Clinical Features - Jenilkumar H. Patel; Nicholas Mankowski; Robbie A. Beyl; Manal S. Malik; Andrew Parker; Edward D. McCoul (OTO Open, 2025)
Abstract Objective Postnasal drip (PND) is a common symptom that is difficult to verify with a traditional examination. Nasal endoscopy has the potential to improve the diagnostic process by confirming the presence and location of mucus. This study sought to describe the association of specific features of PND on nasal endoscopy with other clinical features. Study Design Cross‐sectional with prospective data collection. Setting Outpatient rhinology practice. Methods Data were prospectively collected on adult (≥18 years of age) patients with PND who underwent nasal endoscopy over a 6‐month period. Variables of interest included reflux‐related symptoms, nasal congestion, hyposmia, rhinorrhea, pruritic symptoms, inferior turbinate (IT) hypertrophy, 22‐item sinonasal outcome test (SNOT‐22) scores, and diagnoses of allergic rhinitis (AR), chronic rhinosinusitis (CRS), and reflux disease. Presence of mucus was designated at the nasal cavity (NC) floor, posterior IT, middle meatus (MM), and sphenoethmoidal recess (SER), and consistency of thick or thin was assigned during nasal endoscopy. Results Of 118 patients, 112 (94.9%) had identifiable mucus on nasal endoscopy. MM/SER mucus was associated with SNOT‐22 score ≥ 50, diagnosis of CRS, and absence of IT hypertrophy or diagnosis of AR. NC and IT mucus was associated with nasal congestion, rhinorrhea, pruritic symptoms, IT hypertrophy, AR, and absence of CRS. Thick NC/IT mucus was associated with reflux symptoms. Conclusion Great majority of patients who report PND have posterior nasal drainage of abnormal mucus that can be directly observed with nasal endoscopy. Clinicians should be encouraged to utilize nasal endoscopy when available to evaluate patients with PND.